Cultivating Value Creation. (May 2022) - Davidow, Moshe
This article takes a critical look at what is holding organizations back from implementing value creation. It highlights some of the current misguided thinking of the past 20 years and suggests ways to change the thinking. The financial benefit of these changes is discussed, and ideas for the implementation of a new value creation culture based on complaint management are suggested. It is now up to the managers to implement.